2006
DOI: 10.1001/archderm.142.6.685
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy for Evaluation and Treatment of Patients With Merkel Cell Carcinoma

Abstract: To determine the diagnostic accuracy and usefulness of sentinel lymph node biopsy (SLNB) and computed tomographic scans in the initial evaluation and treatment of patients with Merkel cell carcinoma (MCC).Design: Single-institution case series and literaturebased case-level meta-analysis.Setting: Academic cutaneous oncology clinic.Patients: Sixty-one adults with biopsy-proven MCC (30 who had undergone SLNB) plus 92 cases from the literature of patients who had undergone SLNB.Main Outcome Measures: Relapse-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
235
0
18

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 354 publications
(264 citation statements)
references
References 29 publications
11
235
0
18
Order By: Relevance
“…25 Approximately 33% (20 of 60) had a positive biopsy result and of these patients, only 1 had an isolated regional disease recurrence that occurred in the untreated contralateral neck. 27 A series of previously unpublished cases from the Dana-Farber Cancer Institute of 30 patients who underwent SLNB reported a 30% (9 of 30) lymph node positivity rate, 24 and there was 1 lymph node recurrence in this group. Maza et al reported on 11 patients with microscopic lymph node involvement by positive SLNB 28 ; 3 patients developed recurrence, however, none of them were lymph node recurrences.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…25 Approximately 33% (20 of 60) had a positive biopsy result and of these patients, only 1 had an isolated regional disease recurrence that occurred in the untreated contralateral neck. 27 A series of previously unpublished cases from the Dana-Farber Cancer Institute of 30 patients who underwent SLNB reported a 30% (9 of 30) lymph node positivity rate, 24 and there was 1 lymph node recurrence in this group. Maza et al reported on 11 patients with microscopic lymph node involvement by positive SLNB 28 ; 3 patients developed recurrence, however, none of them were lymph node recurrences.…”
Section: Discussionmentioning
confidence: 92%
“…More recently, SLNB has become standard of care for MCC based on several reports and meta-analyses. [23][24][25] It is particularly appropriate in this disease given its predilection for occult lymph node involvement. SLNB is now recommended in the National Comprehensive Cancer Network guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al reported that the recurrence rate was three times higher in patients who were SLNB positive compared with an SLNBnegative group. 7 Interestingly, a statistically significant association was found between SLNB status and recurrence and survival in the largest singlecenter study. 8 Fields et al reported that the presence of lymphovascular invasion was a strong predictor of SLNB positivity.…”
Section: Discussionmentioning
confidence: 90%
“…Thus far three systematic reviews have addressed lymphatic mapping in MCC [4,18]. Mehrany et al in the 2002 systematic review gathered all cases of sentinel node mapping in MCC by comprehensive search of the literature.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Sentinel node mapping is an important technique for regional lymph node staging in many solid tumors which has also been used for MCC [4].…”
Section: Introductionmentioning
confidence: 99%